2007
DOI: 10.1021/jp0706230
|View full text |Cite
|
Sign up to set email alerts
|

Local Probe and Conduction Distribution of Proton Exchange Membranes

Abstract: Proton exchange membranes (Nafion) have been studied using current sensing atomic force microscopy to examine the correlation between the surface morphology and the ionic domains, and to probe the local ionic conduction distribution in the membranes. It is found that the local ionic conduction generated from the current sensing images follows a Gaussian-like distribution, with the peak value and the width of the distribution increasing with the relative humidity in the sample chamber and, thus, the water conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 39 publications
4
62
0
Order By: Relevance
“…Of great interest is the observation that the conductance distributions derived from the integral current of the entire area show Gaussian fits as opposed to random surface height distributions. Similar to the results obtained in our study, a Gaussian current distribution was also observed for both Nafion Ò 112 and Nafion Ò 117 proton-exchange membranes [13]. The conduction distribution may provide information about inner ionic channels because the current flow may spread largely inside the membrane.…”
Section: Resultssupporting
confidence: 89%
“…Of great interest is the observation that the conductance distributions derived from the integral current of the entire area show Gaussian fits as opposed to random surface height distributions. Similar to the results obtained in our study, a Gaussian current distribution was also observed for both Nafion Ò 112 and Nafion Ò 117 proton-exchange membranes [13]. The conduction distribution may provide information about inner ionic channels because the current flow may spread largely inside the membrane.…”
Section: Resultssupporting
confidence: 89%
“…Although the water meniscus may also increase the contact area between the tip and the ionic clusters due to water condensation at high RH, the primary contribution to the increased current value arises from the increased proton conductance through the ionic network in the membrane 44,61 and the increased surface ionic conductivity (i.e., more ionic groups are available to facilitate proton transport through the membrane) when the membrane becomes more hydrated. 33,61,62 To determine the fraction of conducting active area (f aa ), the current-sensing images must be deconvoluted into conductive and nonconductive regions.…”
Section: Bulk Ionic Conductivity Measurementsmentioning
confidence: 99%
“…This is an important area for future study, in which in situ electrochemical (and associated) techniques will play a vital part. Techniques combining AFM with electrochemical measurements have recently been developed for the study of 37 the ionically conductive channels in proton-exchange membrane, 55 and these may have uses in MFC studies.…”
Section: Scanning Tunnelling Microscopy (Stm) and Atomic Force Microsmentioning
confidence: 99%